To solve the problem step by step, we start with the equation:
Step A: Determine the value of \(c\) that makes the equation a perfect square trinomial.
We are given the equation:
\[ x^2 - 18x = -80 \]
We want to rewrite it in the form \(x^2 - 18x + c = -80 + c\).
To complete the square, we need to take half of the coefficient of \(x\) (which is \(-18\)), square it, and add it to both sides:
- Half of \(-18\) is \(-9\).
- Squaring \(-9\) gives \(81\).
Thus, \(c = 81\).
Step B: Factor the perfect square trinomial.
Now we rewrite the equation with \(c\):
\[ x^2 - 18x + 81 = -80 + 81 \]
This simplifies to:
\[ x^2 - 18x + 81 = 1 \]
Now we can factor the left side:
\[ (x - 9)^2 = 1 \]
Step C: Solve the equation for the lesser solution.
To find the solutions for \(x\), we take the square root of both sides:
\[ x - 9 = \pm 1 \]
This gives us two equations:
- \(x - 9 = 1\)
- \(x - 9 = -1\)
Solving these:
- \(x = 1 + 9 = 10\)
- \(x = -1 + 9 = 8\)
The lesser solution is:
\[ \text{Lesser solution: } x = 8 \]
Step D: Solve for the greater solution.
The greater solution is:
\[ \text{Greater solution: } x = 10 \]
Final Answers:
A. \(c = 81\)
B. The equation is \((x - 9)^2 = 1\)
C. Lesser number solution: \(x = 8\)
D. Greater number solution: \(x = 10\)